MENINGKATKAN PARTISIPASI SISWA MELALUI IMPLEMENTASI ICE BREAKING VIRTUAL DALAM PEMBELAJARAN ONLINE - Bella Anisa, Salsa; Noviatul Hikmah; Sukmawati , Wati; Dwi Tarishah, Salwa; Fatiya, Salwa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education in Indonesia is facing significant challenges due to the COVID-19 pandemic, which has forced the learning process to move online. This has a negative impact on students' learning motivation and concentration, as well as giving rise to various technical and psychological obstacles. Action research in the classroom was carried out to address this issue. to explore the application of virtual ice breaking as a method to increase student motivation in online learning to reactivate their interest and enthusiasm for learning. This method is designed to provide a fun and interactive break in the middle of a lesson, so that students can be more focused and actively involved in the online learning process. The research method uses observation, questionnaires to students, and interviews with students' parents as data collection techniques. The research results show that virtual ice breaking is effective in creating a fun learning atmosphere and encouraging students to actively participate. Thus, this approach has the potential to improve overall student learning outcomes, overcome challenges in online learning, and assist educators in achieving learning goals.